Media’s Role in Promoting Voting Participation: A Case Study on Zilla Parishad Election - Sultana, Mst. Rajia (The Jahangirnagar Review, 2024)
The role of media and democratic elections are inextricably related. Focusing on the Zilla Parishad Election in 2022, the study explores the roles of media to promote voting participation like conducting free and fair election, making voter awareness, candidate identity, creating election environment such as evaluation of election manifesto, positive and negative campaign techniques, maintaining a code of conduct and ensuring accountability of concerned election officials. In this study, data have been collected from primary and secondary sources and qualitative and quantitative research methods have been applied. The information of three categories of population in Zilla Parishad elections like general voters, elected representatives and journalists is investigated here. Based on open ended answer from a representational survey directed during election campaign from combination of interviewed data analysis, media shapes voting behavior by reconfigures reinforcing believe, agenda setting and reporting violence incidents related to electoral corruption. Notably, The findings suggest that media plays a massive role in promoting voting participation which establishes a participatory society.